Analysis of The Quality of Financial Statements: a Case Study of Rutong Village in 2019-2023 - Ardiansyah, Ardiansyah; Umarella, Barus; Salis, M. Rizkoni (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This study analyzes the quality of financial statements against the report on the realization of the APBDes in Rutong Country for the 2019”“2023 period. Data collection techniques are in the form of interviews and documentation. The analysis was carried out qualitatively with an evaluation approach on four aspects of financial report quality, namely relevance, reliability, ability to compare, and ease of understanding. The results of the study show that the Rutong State financial statements have fulfilled their relevance by providing useful information for decision-making, and reliability through the presentation of accurate figures. The ability to compare is reflected in the consistency of the report format from year to year, while the ease of understanding still needs to be improved through the simplification of technical terms. The study also identifies key challenges in managing financial statements, such as limitations in human resource competence and information technology implementation. This study provides recommendations for optimizing budget planning based on priority needs to reduce the deviation between budget and realization, especially in the field of development and community empowerment. Financial statements should be equipped with historical data to make it easier to analyze trends and evaluate performance. To increase participation, reports are presented with a glossary or executive summary in plain language. Regular evaluations and continuous training for village officials need to be carried out so that financial management is in accordance with standards. In addition, a focus on program efficiency and effectiveness is needed to ensure that budget allocations provide optimal benefits, especially in the areas of development and health, in order to support sustainable development.